(untitled) (South East Asia Journal of Public Health, 2016)
Further utilization of hospital facility is influenced by the provision of hospital care and cost of services. This study was conducted among patients of public and private hospitals of Dhaka city, Bangladesh to explore the relationship of further utilization of hospital care and cost of services incurred during previous visits. A total 199 patients of 2 private and 2 public hospitals were included. Of them, 100 (50.25%) were from public and 99 (49.74 %) from private hospitals. Male: female ratio of the respondents was 111:88. The level of services was scored by patients on a 1-5 Likert scale on the aspects of services of doctors, nurses, other staffs; medicine supply; cleanliness; and investigation facilities. Poor people usually sought the services from public hospitals. About three-quarter of the respondents (76.9 %) mentioned that they would avail the facility of same hospital for their further ailment. Seventeen patients (17%) who were treated in government hospitals will not further utilize the services, and this was significantly higher (p-0.02) in the case of patients from private hospitals (29.3%). Regression analysis explored that quality of services (p=-0.000) and cost of services (p=0.001) influenced the plan of future consumption of hospital facility and quality of services having stronger influences. This study concludes that further utilization of the hospital facility was strongly influenced by the quality of services and next to that is cost of services. So we recommend for best and successive utilization of hospital services to improve facilities and minimization of cost are the essential needs. South East Asia Journal of Public Health Vol.6(1) 2016: 14-19